Interfaces entre a maturidade da economia circular em empresas estabelecidas no Brasil: o papel do Green Human Resource Management, Green Supply Chain Management, produção enxuta e o efeito moderador da gestão do conhecimento - Moraes, Tiago Estrela da Cunha [UNESP] (2023)
This dissertation has as its central objective the analysis of the Maturity of the Circular Economy in Brazilian organizations, highlighting its interconnections with other fields of study. The focus is on the integration between theory and business practice. To achieve this purpose, a comprehensive literature review was carried out on Circular Economy Maturity and its possible visualization with areas such as: Total Quality Management (TQM), Lean Manufacturing (LM), Green Supply Chain Management (GSCM), Green Human Resources Management (GHRM) and Knowledge Management. This theoretical basis served as the foundation for the construction of validated questionnaires, which played a central role in the empirical phase of the research, adopting the data collection methodology (survey). The results obtained, for the most part, contradict what was expected in the literature, although other relevant findings also emerged and are duly concluded. In this context, this study provides a significant contribution by presenting a practical proposal for professionals seeking to integrate widely recognized practices (GHRM, TQM, LM, GSCM and Knowledge Management) with the principles of the Circular Economy, providing tangible paths for its effectiveness in organizations. Furthermore, at a global level, this research fills an important gap in the existing body of knowledge and lays solid foundations, opening paths that prove to be of great relevance for a future research agenda in the field.